An Economics Approach to Modeling the Productivity of Computer Systems - Kriebei, Charles H.; Raviv, Artur (Management Science, 1980)
The problem of linking computing and information services to end user needs for performance evaluation has been a long standing issue in the systems literature. A joint university-industry research project was begun in 1975 to better understand the problem. The specific goals of the project have been: (1) to develop a theory or conceptual framework for productivity measurement of the computing and information services function, (2) to pilot test the theory through empirical analysis at field sites, and (3) to evaluate the results and report the conclusions (success and failure). This paper is addressed to the first of these goals; the empirical tests and experience based on the framework are reported in a sequel paper. Our approach to modeling the productivity of computer systems is based on conventional economic theory and empirical analysis. The economics paradigm is to view the organization as a marketplace for computing and information services which contains elements of supply and demand. In this paper our concern centers on the supply of services. A model of the production process for computing services available within an organization is developed which quantitatively relates input resources and output products or services; the model also incorporates output quality as an integral function of the relevant variables in the process. Various measures of production efficiency are defined based on this model. The productivity of a computer system is defined in terms of these measures and we discuss their application for administrative decisions in performance evaluation.